Profil Perempuan dalam Usaha Ekonomi Produktif (Kajian Profil Wanita Tani Dalam Usahatani Ternak Sapi Potong Rakyat di Desa Pagak Kecamatan Sumberlawang Kabupaten Sragen) - Suminah Suminah (Universitas Sebelas Maret, 2003)
This research aims to: (1) getting data about woman farmer profile characteristic which managing beef cattle farm; (2) identifying requirement, supplementary and resistor factor of woman farmer in beef cattle farm development; and (3) to formulate the appropriate effort intervention to woman in management of beef cattle farm.It is descriptive method which used to explain woman farmer which managing beef cattle farm in Pagak village Sumberlawang Region Sragen District. Data was collected by interview technique with relevant stakeholders, interview with woman farmer which managing beef cattle farm to know their characteristic, FGD (Forum Group Discussion) with women farmer which managing beef cattle farm.Result of this research are: first, description of woman farmer profile manage beef cattle farm covering age, formal education, non-formal education, amount of cattle had, and status of ownership of cattle. Second, requirement, supplementary and resistor factor is known to relate at Seven Program of beef cattle farm i.e. election of seed, ready of woof, house, reproduction, management, time after harvest and marketing. Third, that woman farmer which managing beef cattle farm have big role in improving economic earnings of family, so that woman farmer require to be powered by unionized of grouping; then give them by training related to reinforcement their group, especially training of beef cattle farm woof ferment.